2017
DOI: 10.5152/turkthoracj.2017.16023
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Working in a Smoke-Free Workplace on use of Smoking and Smokeless Tobacco

Abstract: OBJECTIVES:The aim of this study was to evaluate whether smokeless tobacco (Maras powder) use increased among smokers working at smoke-free workplaces or not. MATERIAL AND METHODS:In Kahramanmaraş city, 242 male workers who were current or former smokers, working at strictly smokefree workplaces were included in this study. A total of 21 questions, including the Fagerstrom Test for Nicotine Dependence, were asked. RESULTS:All the participants were male with a mean age of 29.33±6.66 years, and the age range was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Similarly, a statistical difference was found between working group and control group in terms of PD.As these were the first data evaluating PD in respect of ST, to be able to obtain some idea, they were compared with the results of studies conducted with cigarette smokers. Nevertheless, even if the smoke and toxic effects of cigarettes are discounted, the nicotine content of ST is approximately 6-10 fold higher than that of cigarettes (2)(3)(4)(5)(6)(7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a statistical difference was found between working group and control group in terms of PD.As these were the first data evaluating PD in respect of ST, to be able to obtain some idea, they were compared with the results of studies conducted with cigarette smokers. Nevertheless, even if the smoke and toxic effects of cigarettes are discounted, the nicotine content of ST is approximately 6-10 fold higher than that of cigarettes (2)(3)(4)(5)(6)(7).…”
Section: Discussionmentioning
confidence: 99%
“…The nicotine concentration in this tobacco plant is approximately 6-10 fold higher than that of the tobacco used in cigarette production. By wetting the mixture, the wetness ratio is increased to increase absorption from the oral mucosa (4)(5)(6). The mixture is used by placing a small amount (up to 1 gr) inside the mouth between the gums and the lower or upper labial mucosa, or sometimes below the tongue (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a systematic review in the British Medical Journal showed that smoke­free workplaces are associated with reductions in the prevalence of smoking of 3.8% and 3.1 fewer cigarettes smoked per day per continuing smoker [ 12 ]. Kahraman et al found that working in SF workplaces was associated with increased rates of quitting smoking and with increased use of Maras powder, which is a local form of oral smokeless tobacco in Turkey [ 13 ].…”
Section: Introductionmentioning
confidence: 99%